The potential impact of COVID-19-related disruption on tuberculosis burden - McQuaid, C. Finn; McCreesh, Nicky; Read, Jonathan M.; Sumner, Tom; Houben, Rein M.G.J.; White, Richard G.; Harris, Rebecca C. (The European respiratory journal, 2020)
Before the coronavirus disease 2019 (COVID-19) pandemic, over 4000 people were dying from tuberculosis (TB) every day [1]. As with past emergencies [2], the impact of COVID-19 on TB outcomes is a serious cause for concern [3] but is currently unknown. Health system overload, due to high numbers of COVID-19 cases, as well as interventions necessary to limit the transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), could result in severe reductions in health service availability and access for the detection and treatment of TB cases [4]. However, physical distancing interventions could also limit Mycobacterium tuberculosis transmission outside of households, where most transmission occurs [5]. This has not been adequately explored in concurrent work [6–8], and it is currently unclear whether social distancing could compensate for disruptions in TB services, and what the impact of these combined COVID-19 disruption effects on TB burden is likely to be. Any benefit of social distancing on TB deaths is likely to be outweighed by health service disruption. As such, it is crucially important to maintain and strengthen TB-related health services during, and after, the COVID-19 pandemic. https://bit.ly/30aWZnp